Strategi Pencatatan Keuangan sebagai Langkah Awal Menuju Kemandirian Ekonomi: Sinergi Kewirausahaan dan Perpajakan - Gunardi Gunardi; Yani Ramdani; Siti Mialasmaya; Eri Febriani (PADMA, 2025)
Proper financial recording is essential to achieve economic independence, especially for Micro, Small, and Medium Enterprises (MSMEs). This community service program (PKM) provides training on basic financial recording, creative entrepreneurship, and understanding MSME tax obligations under Government Regulation No. 55 of 2022. The methods include manual and digital recording education, tax calculation simulations, and developing local potential-based business ideas with simple digital promotion strategies. The results showed improved participant understanding in financial recording and business strategy development. This program is expected to support sustainable economic independence in the community.